The relation between mother's socio-economic status and daughter's fertility intentions in Austria, Italy, Bulgaria, and Norway - Maria Rita Testa; Valeria Bordone; Beata Osiewalska; Vegard Skirbekk (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2016)
Fertility intentions are the most proximate determinants of actual fertility (e.g., Barber 2001; Bongaarts 1992) and inform us about directional trends (Hin et al. 2011; Testa 2014). They are transmitted across generations from parents to children (Fernandez and Fogli 2006). However, the literature on intergenerational transmission of fertility has viewed the effect of the family of origin mainly in terms of sib-ship size; that is women with more siblings are likely to have more children (e.g., Murphy and Knudsen 2002). In this paper we argue that young female adults may refer to their mothers' experience as a model - either to aim for or to be avoided - when forming their own fertility intentions. More specifically, we test whether there are positive intergenerational effects of education on intended childbearing: the more children highly educated women have, the more children highly educated women in the daughter's (subsequent) generation will plan to have because they have witnessed how combining family and occupational career is a realistic life target for many women/mothers with high education. [...]
Keywords: 300